ZCCHC8 p.P410A disrupts nucleocytoplasmic localization, promoting idiopathic pulmonary fibrosis and chronic obstructive pulmonary disease - Chen-Yu Wang; Si-Hua Chang; Cheng-Feng Hu; Yi-Qiao Hu; Hong Luo; Lv Liu; Liang-Liang Fan (BMC, 2024)
Abstract Background Idiopathic pulmonary fibrosis (IPF) is a special kind of chronic interstitial lung disease with insidious onset. Previous studies have revealed that mutations in ZCCHC8 may lead to IPF. The aim of this study is to explore the ZCCHC8 mutations in Chinese IPF patients. Methods Here, we enrolled 124 patients with interstitial lung disease from 2017 to 2023 in our hospital. Whole exome sequencing and Sanger sequencing were employed to explore the genetic lesions of these patients. Results Among these 124 patients, a novel mutation (NM_017612: c.1228 C > G/p.P410A) of Zinc Finger CCHC-Type Containing 8 (ZCCHC8)was identified in a family with IPF and chronic obstructive lung disease. As a component of the nuclear exosome-targeting complex that regulates the turnover of human telomerase RNA, ZCCHC8 mutations have been reported may lead to IPF in European population and American population. Functional study confirmed that the novel mutation can disrupt the nucleocytoplasmic localization of ZCCHC8, which further decreased the expression of DKC1 and RTEL1, and finally reduced the length of telomere and led to IPF and related disorders. Conclusions We may first report the ZCCHC8 mutation in Asian population with IPF. Our study broadens the mutation, phenotype, and population spectrum of ZCCHC8 deficiency.